Modeling incomplete penetrance in arrhythmogenic cardiomyopathy by human induced pluripotent stem cell derived cardiomyocytes - De Bortoli, Marzia; Meraviglia, Viviana; Mackova, Katarina; Frommelt, Laura S.; König, Eva; Rainer, Johannes; Volani, Chiara; Benzoni, Patrizia; Schlittler, Maja; Cattelan, Giada; Motta, Benedetta M.; Volpato, Claudia; et al. (Computational and structural biotechnology journal, 2023)
Human induced pluripotent stem cell derived cardiomyocytes (hiPSC-CMs) are commonly used to model arrhythmogenic cardiomyopathy (ACM), a heritable cardiac disease characterized by severe ventricular arrhythmias, fibrofatty myocardial replacement and progressive ventricular dysfunction. Although ACM is inherited as an autosomal dominant disease, incomplete penetrance and variable expressivity are extremely common, resulting in different clinical manifestations. Here, we propose hiPSC-CMs as a powerful in vitro model to study incomplete penetrance in ACM. Six hiPSC lines were generated from blood samples of three ACM patients carrying a heterozygous deletion of exon 4 in the PKP2 gene, two asymptomatic (ASY) carriers of the same mutation and one healthy control (CTR), all belonging to the same family. Whole exome sequencing was performed in all family members and hiPSC-CMs were examined by ddPCR, western blot, Wes™ immunoassay system, patch clamp, immunofluorescence and RNASeq. Our results show molecular and functional differences between ACM and ASY hiPSC-CMs, including a higher amount of mutated PKP2 mRNA, a lower expression of the connexin-43 protein, a lower overall density of sodium current, a higher intracellular lipid accumulation and sarcomere disorganization in ACM compared to ASY hiPSC-CMs. Differentially expressed genes were also found, supporting a predisposition for a fatty phenotype in ACM hiPSC-CMs. These data indicate that hiPSC-CMs are a suitable model to study incomplete penetrance in ACM. [Display omitted]